Virtual simulations to address cultural responsiveness of nutrition and dietetic students: a feasibility study - Hunter, Elizabeth; Hazim, Kohrine; Lok, Benjamin C.; Andrade, Jeanette M. (Frontiers in Education, 2025)
IntroductionVirtual simulations have been used in various healthcare fields to enhance knowledge and technical skills. Few focus on enhancing personal skills like cultural responsiveness. The purpose of this study was to assess the feasibility of using virtual simulations to enhance cultural responsiveness among nutrition and dietetic undergraduate students.MethodsTwo virtual simulations were developed using Dialogflow and Synthesia software. Both simulations had virtual agents who had chronic kidney disease and another chronic condition and were considered diverse - financial status, age, gender, and race/ethnicity. Content matter experts reviewed the scenarios and potential questions that a student would ask and the responses for accuracy and relevance. Nutrition and dietetic undergraduate students (n = 55) completed a 5-item open-ended survey regarding ease, difficulty, likes, dislikes, improvements of the simulations, and a closed ended question on a 5-point Likert scale towards agreement with cultural responsiveness. NVivo v14 was used to analyze the transcripts from the interaction with the agents and the responses from the survey using conceptual content analysis.ResultsParticipants indicated that the two simulations were easy to use. Some difficulties identified were the inability to get a response from the agents. From the transcript analysis, the main themes that participants asked the virtual agents were focused on lifestyle, eating habits, finances, and general medical. Participants (72%) agreed/strongly agreed that their cultural responsiveness improved.ConclusionVirtual simulations may be a method to enhance cultural responsiveness. Further research should be conducted to determine if these virtual simulations help students apply cultural responsiveness when working with clients.